(untitled) (ModaPalavra e-periódico, 2025)
This article aims to discuss the difficulties faced in the management of production processes of original fashion brands in the state of Goiás (GO) and is the result of the first qualitative analyses carried out during the year 2024, within a broader research project on individual microentrepreneurship in the clothing manufacturing sector in the Central-West region of Brazil. To this end, bibliographic and documentary research was methodologically carried out in government data and websites/social networks of some original brands, of an exploratory and descriptive nature, with an emphasis on the qualitative approach, to survey the complexity of the management of production processes faced by these companies managed by individual microentrepreneurs in the region in question. In this sense, the theme is considered relevant to the fashion area, whose critical analysis allowed to point out challenges that can be faced to improve the productive efficiency of original brands based on the mapped scenario.